2021
DOI: 10.1017/ehs.2021.28
|View full text |Cite
|
Sign up to set email alerts
|

Permutation test applied to lexical reconstructions partially supports the Altaic linguistic macrofamily

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“… Kassian et al (2021) employed the test reported by Turchin et al (2010) , originally inspired by Dolgopolsky (1964) to another dataste of languages from the disputed Altaic family, with the difference that they used reconstructed proto-languages. Their test also failed to provide conclusive evidence for the whole language family, although they argue that rather clear support can be found for a deeper relationship of the families tested by Ceolin (2019) .…”
Section: New and Old Open Problemsmentioning
confidence: 99%
See 2 more Smart Citations
“… Kassian et al (2021) employed the test reported by Turchin et al (2010) , originally inspired by Dolgopolsky (1964) to another dataste of languages from the disputed Altaic family, with the difference that they used reconstructed proto-languages. Their test also failed to provide conclusive evidence for the whole language family, although they argue that rather clear support can be found for a deeper relationship of the families tested by Ceolin (2019) .…”
Section: New and Old Open Problemsmentioning
confidence: 99%
“…Their test also failed to provide conclusive evidence for the whole language family, although they argue that rather clear support can be found for a deeper relationship of the families tested by Ceolin (2019) . While both Ceolin (2019) and Kassian et al (2021) applied methods proposed before to newly compiled datasets, Blevins and Sproat (2021) designed a new workflow for to test for supposed deep language relations in order to find evidence for the hypothesis that the language isolate Basque is related to Indo-European. In contrast to previous studies, Blevins and Sproat (2021) test their approach on a rather large sample of languages where the language relations are known, showing that their approach is rather conservative, showing a tendency to reject grouping two languages within the same family in case of sparse evidence.…”
Section: New and Old Open Problemsmentioning
confidence: 99%
See 1 more Smart Citation
“…The formation and dispersion of the Oirats is connected with the Altai-Sayan highlands, which were under the influence of several political formations during 13th-18th centuries AD, including the Oirat Khanate [3]. The common history has left traces in the linguistics [18] as well as in the cultural layers of the Oirats and Altaians [3], but their genetic ties have not yet been studied.…”
Section: Introductionmentioning
confidence: 99%